Certain Classes of Meromorphically Univalent Functions Associated With Subordinaion and Inclusion Relations - Meena, Krisn Pratap; Bapna, Indu Bala (Communications in Mathematics and Applications, 2024)
In this present paper, we introduce some new classes of Meromorphic function in punctured unit disk involving integral operator. Our concern is to study some useful characteristic properties for the above defined general integral operator with applications of meromorphic function.
Keywords: Meromorphic functions; Hadamard product; Subordination; Univalent functions; Integral operator